SIGNIFICANCE OF ADDITIONAL CHROMOSOMAL ABNORMALITIES FOR THE OUTCOMES AFTER THE SECOND LINE NILOTINIB THERAPY IN THE CHRONIC MYELOID LEUKEMIA PATIENTS - Dmytrenko, I. V.; Minchenko, Zh. M; Fedorenko, V. V.; Dyagil, I. S. (International Journal of Medicine and Medical Research, 2019)
Background. There is limited information about impact of additional chromosome aberrations (ACA) on the efficacy of the 2nd line nilotinib therapy. Objective. The aim of the study was to analyze significance of ACAs for the outcome after second line tyrosine kinase inhibitors (TKI) therapy with nilotinib in the chronic myeloid leukemia (CML) patients, who experienced previous imatinib therapy failure. Methods. The CML patients in chronic phase treated with nilotinib after imatinib failure were analyzed for outcomes. Results. Among a total of 114 patients, 18 patients (15.8%) had ACAs at the beginning of the 2nd line therapy with nilotinib. Seven patients (38.9%) of 18 had variant translocations and 11 patients (61.1%) had other chromosomal abnormalities in addition to t(9;22), known as clonal evolution. Complete cytogenetic response (CCR) at 12 months was achieved in 37.5%, 42.8% and 45.5% (p=0.842) of patients with classic t(9;22) translocation, variant translocations and ACAs respectively. In the patients with variant translocations t(9;V;22) or clonal evolution treated with nilotinib after the imatinib failure, the CCR and major molecular response (MMR), event free survival (EFS), progression free survival (PFS) and overall survival (OS) rates did not differ from those in the CML patients with t(9;22) only. At the same time quantitative characteristics of leukemic and ACA clones had prognostic value for CCR. The increased number of Ph-positive cells and the number of cells with the ACA at the start of nilotinib therapy reduced the probability of CCR. Conclusions. Higher nilotinib inhibitory activity compare with imatinib allows us to overcome imatinib resistance in the CML patients regardless of the ACA presence at the beginning of nilotinib therapy.